(untitled) (KYAMC Journal, 2017)
Hormonal changes and maternal demands during pregnancy result in marked changes in maternal thyroid activity. It has been suggested that the thyrotropic effect of hCG in pregnancy increases thyroid activity in addition of thyrotropic effect of TSH. To compare the serum levels of thyroid stimulators (hCG & TSH) and thyroid hormones (T3 & T4)) in normal pregnant women and thus to clarify the role of hCG & TSH on thyroid function in pregnancy, we measured serum hCG, TSH, total T3 & T4 and free T3 & T4 concentrations in the serum samples of 32 pregnant women in their different trimesters and in the serum samples of 22 non-pregnant normal female control. Serum total T3 & T4 were significantly elevated throughout pregnancy in comparison with controls. Free T4 level was elevated at 1st trimester but reduced in 2nd and 3rd trimesters. The free T3 levels were remained unchanged throughout pregnancy and no significant change in pregnancy than non pregnant control. Serum TSH levels were significantly lower at 1st trimester compared to 2nd and 3rd trimester of the pregnancy. Serum hCG levels were highest in 1st trimester. We conclude that hCG, as a weak thyroid stimulator, causes moderate increase in free thyroid hormone levels in 1st trimester which in turn causes a moderate reduction in TSH levels in early pregnancy. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 623-626